Die Diözese der Armenischen Kirche in Deutschland und ihre Erfahrungen in Mission und Ökumene - Sardaryan, Diradur (Catholica <Münster>, 2022)
The Armenian Apostolic Church, one of the oldest churches in the world, has been present in Germany since the end of World War II. The article informs about its history and development in Germany, the current structure of the Armenian Diocese in Germany and gives some examples for its concern for the spiritual needs of the Armenian people. Finally, the intensive ecumenical commitment of the Armenian Apostolic Church is highlighted, which could still find a greater resonance in society as well as in the Catholic and Protestant Churches.